A study of the prognosis of patients with limited-stage small cell lung cancer who did or did not receive prophylactic cranial irradiation after effective chemoradiotherapy - Wu, Qing; Chen, Mengyuan; Peng, Fang; Zhang, Qun; Kong, Yue; Bao, Yong; Xu, Yujin; Hu, Xiao; Chen, Ming (Frontiers in Oncology, 2023)
Objective To investigate the prognosis of patients with LS-SCLC who responded to chest chemoradiotherapy but did not receive PCI. Methods A retrospective analysis was conducted on LS-SCLC patients who had achieved complete remission (CR) or partial remission (PR) after definitive chemoradiotherapy but did not receive PCI. The survival rates were calculated using Kaplan–Meier method. The prognosis was analyzed using Cox proportional hazard regression model. The main endpoint was OS. Results Of the 500 patients with LS-SCLC admitted between June 2002 and January 2018, 327 achieved CR or PR after definitive chest chemoradiotherapy, 103 did not receive PCI, and 63 of them developed brain metastases (BM). The 1-year and 3-year OS rates in PCI group were 87.5% and 42.3% respectively, versus 70.4% and 20.9% for non-PCI group(P=0.002). The median survival time after BM was 8.7 months (range: 0.3-48.7), and 3-year OS rate was 15.0%, the median survival time of patients without BM was 20.1 months (range: 2.9-79.4), and 3-year OS was 33.4% (P=0.014). Patients with BM were subsequently treated with palliative therapy. Multivariate analysis showed that compared with no treatment, brain radiotherapy alone (HR: 0.131, 95%CI: 0.035-0.491，P=0.003) and radiotherapy combined with chemotherapy (HR: 0.039, 95%CI: 0.008-0.194，P＜0.001) significantly reduced the risk of death. Multiple BM (HR: 2.391, 95%CI: 1.082-5.285，P=0.031) was an independent adverse prognostic factor for OS. Conclusion LS-SCLC patients who achieved good response after chest chemoradiotherapy without receiving PCI were prone to develop BM and have a poor prognosis. Multiple BM was an independent adverse prognostic factor. PCI remains the standard of care for LS-SCLC patients.